Application of digital spectral analysis to decomposition of positron lifetime spectra - Kul'ment'ev, A.I. (Вопросы атомной науки и техники, 2005)
New method of positron annihilation lifetime spectra processing is proposed. It is based on digital spectral analysis, namely, on Prony method. The regularization procedure to solve the inverse problem of finding parameters of useful signals present in the data is formulated. A new approach to determine the number of components in a spectrum is proposed. Results on simulated spectra demonstrate the high-resolution capability of the method.